Polysaccharide Fraction Isolated from Saccharina japonica Exhibits Anti-Cancer Effects Through Immunostimulating Activities - Min Seung Park; Seung-U Son; Tae Eun Kim; Se Hyun Shim; Bong-Keun Jang; Sunyoung Park; Kwang-Soon Shin (Marine Drugs)
The present research aimed to assess the anti-cancer effects of the polysaccharide fraction (SJP) isolated from Saccharina japonica. The release of immune-activating cytokines, including IL-6, IL-12, and TNF-α, was markedly stimulated by the SJP in a concentration-dependent manner within the range of 1 to 100 µg/mL. Furthermore, the prophylactic intravenous (p.i.v.) and per os (p.p.o.) injection of SJP boosted the cytolytic activity mediated by NK cells and CTLs against tumor cells. In a study involving Colon26-M3.1 carcinoma as a lung cancer model, both p.i.v. and p.p.o. exhibited significant anti-lung-cancer effects. Notably, p.i.v. and p.p.o. administration of SJP at a dose of 50 mg/kg reduced tumor colonies by 84% and 40%, respectively, compared to the control. Moreover, the anti-lung-cancer effects of SJP remained substantial, even when NK cell function was inhibited using anti-asialo-GM1. Fractionation with CaCl2 suggested that SJP is a mixture of alginate and fucoidan. The fucoidan fraction stimulated the immune response of macrophages more strongly than the alginate fraction. Consequently, this finding suggested that SJP from S. japonica possesses remarkable anti-cancer effects through the activation of various immunocytes. In addition, this finding indicates that the potent biological activity of SJP may be attributed to fucoidan.